Capital letters : revealing Wellington's urban history through typographic remnants : a thesis presented in partial fulfillment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand - Haughan, Laura (Massey University, 2012)
Capital Letters uses visual communication design to forge relationships between the city and its past. It draws on the theory of geosemiotics (Scollon & Scollon, 2003) to position typographic remnants found in urban spaces, in time and place. In order to fully understand the semiotic meaning of typographic remnants, their historical context must be uncovered. As indexical signs, their semiotic meaning shifts as their surroundings change. This project examines the role that signage plays in the authentication of local places and highlights their importance as a form of visual cultural history. The city is explored, specific areas are traversed and the typographic discoveries documented. Semiotic archaeology extracts both the individual and the collective memory of the remnants, revealing their narratives and historical context, allowing previously indiscernible connections to be made. Focussing on these connections – the clustering of remnants and their shared indexicality – changes in the urban fabric of the city are revealed, traces of a continuously reshaped environment become apparent. The remnants act as indices to previous times. They inform of topographical changes in the urban fabric of the city and shifts in urban functional zones. Capital Letters uncovers a map of historical change and provides a new way in which to discover the city: through typographical remnants.
Keywords: Signage; Signs on buildings; Historical markers; Wellington buildings; Typography; Visual culture; Urban historical change